Alzheimer’s disease pathogenetic progression is associated with changes in regulated retained introns and editing of circular RNAs - Arizaca Maquera, Karol Andrea; Welden, Justin Ralph; Margvelani, Giorgi; Miranda Sardón, Sandra C.; Hart, Samantha; Robil, Noémie; Hernandez, Alvaro Gonzalo; de la Grange, Pierre; Nelson, Peter T.; Stamm, Stefan (Frontiers in Molecular Neuroscience, 2023)
Introduction The molecular changes leading to Alzheimer’s disease (AD) progression are poorly understood. A decisive factor in the disease occurs when neurofibrillary tangles (NFT) composed of microtubule associated protein tau (MAPT) form in the entorhinal cortex and then spread throughout the brain. Methods We therefore determined mRNA and circular RNA changes during AD progression, comparing Braak NFT stages I-VI. Total RNA was isolated from human brain (entorhinal and frontotemporal cortex). Poly(A)+ RNA was subjected to Nanopore sequencing, and total RNA was analyzed by standard Illumina sequencing. Circular RNAs were sequenced from RNase R treated and rRNA depleted total RNA. The sequences were analyzed using different bioinformatic tools, and expression constructs for circRNAs were analyzed in transfection experiments. Results We detected 11,873 circRNAs of which 276 correlated with Braak NFT stages. Adenosine to inosine RNA editing increased about threefold in circRNAs during AD progression. Importantly, this correlation cannot be detected with mRNAs. CircMAN2A1 expression correlated with AD progression and transfection experiments indicated that RNA editing promoted its translation using start codons out of frame with linear mRNAs, which generates novel proteins. Discussion Thus, we identified novel regulated retained introns that correlate with NFT Braak stages and provide evidence for a role of translated circRNAs in AD development.